An Improved PV Output Forecasting Model by Using Weight Function: A Case Study in Cambodia - Kittisontirak, Songkiate; Bupi, Aekkawat; Chinnavornrungsee, Perawut; Sriprapha, Kobsak; Thajchayapong, Pairash; Titiroongruang, Wisut (My University, 2016)
This paper proposes a new concept to improve accuracy of PV forecasting model. The model was implemented by MATLAB/Simulink software using solar irradiance and module temperature as measurement parameters for calculation. The model was developed by single-diode equivalent circuits (5-p model) for simulated PV module power output and compared with other software programs for validation which showed correct PV characteristics. To achieve high accuracy, the model was improved by weight function using one-year measured data. The accuracy of our developed model was verified by comparison with four commercial simulator software programs and the results from real system which were measured and recorded for 1 year. It was found that the model output was in a good agreement with the measured data. This research can be utilized in another area by adjusting the PV equation with weight function of that area.